AN EFFECT OF SALARY AND FACILITIES ON EMPLOYEE SPIRIT AT PT. BAKRIE SUMATERA PLANTATIONS BRANCH MEDAN - Ikhwana, Hablil; Suriana, Suriana (Proceeding International Conference of Science Technology and Social Humanities; Vol 1 (2022): International Conference of Science Technology and Social Humanities, 2022)
A study must have a purpose, while the general purpose of this research is to find out whether the salary and facilities both partially and simultaneously affect employee morale at PT. Bakrie Sumatera Plantations Medan Branch and how much influence they have.From the results of the research that has been discussed by processing and questionnaires and using several tests it can be concluded that partially, the salary variable (X1) has a significant influence on employee moralePT. Bakrie Sumatera Plantations Medan Branch. This means that the hypothesis in this study is accepted, as evidenced by the t count > t table (33,997> 1,999). While the facility variable (X2) has no significant effect on employee moralePT. Bakrie Sumatera Plantations Medan Branch. This means that the hypothesis in this study was rejected, as evidenced by the value of t count F table (583,968> 3.15). The variable salary (X1) and facilities (X2) is able to contribute to the influence of the employee morale variable by 95% while the remaining 5% is influenced by other variables not examined in this study